1). (pvq) y(p^q) n=4,6 L. 2). (Pvq) y(pq) n=4,8 L 3). (Pvq) y(p^q) n=4,3L. 4). (Pvq) y(p^ q) n=4,5 L 5). (Pvq) y(paq) n=

1). (pvq) y(p^q) n=4,6 L.
2). (Pvq) y(pq) n=4,8 L
3). (Pvq) y(p^q) n=4,3L.
4). (Pvq) y(p^ q) n=4,5 L
5). (Pvq) y(paq) n=4,2 L
6). (pvq) y(paq) n=4,7L
7), (Pvq) y (p^q)n=4,9 L
8). (Pvq) y(p^ q) n=4, 10 L
9). (pvq) y(paq) n=4,4 L
10).(Pvq) y(paq İn=4 12L
11). (Pvq) y(p^q)n=4 11 L
12). ( Pvq) y paq) n=4 13 L​

1 comentario en «1). (pvq) y(p^q) n=4,6 L. 2). (Pvq) y(pq) n=4,8 L 3). (Pvq) y(p^q) n=4,3L. 4). (Pvq) y(p^ q) n=4,5 L 5). (Pvq) y(paq) n=»

Deja un comentario